Inventarisasi Karakteristik Biofisik dan Strategi Pengelolaan Lahan Marginal Dataran Banjir di Nagari Duku Kabupaten Pesisir Selatan - Afdiron Novinda; Peri Hariyanto; Andika Firma Deni; Sritirta; Jamilah; Osronita (Jurnal Ragam Pengabdian, 2026)
Floodplain marginal lands are constrained by complex interactions between soil properties and hydrological regimes, limiting their agricultural productivity without targeted management interventions. This study aimed to characterize marginal land conditions in Nagari Duku, Koto XI Tarusan Sub-district, Pesisir Selatan Regency, to support the formulation of sustainable land management strategies. A structured literature-based analysis was conducted by synthesizing recent studies on floodplain hydrology, soil physical and chemical characteristics, and flood vulnerability mapping derived from geospatial and digital soil datasets. Soil attributes and flood dynamics were interpreted using government reports, peer-reviewed publications, and regional flood modeling studies representing comparable geomorphological and land-use conditions. The findings indicate that Nagari Duku constitutes an active floodplain dominated by sandy loam soils with relatively high bulk density, low porosity, low organic carbon content (approximately 1.3–1.6%), and strongly acidic soil reaction (pH 4.5–4.9). The landscape is further characterized by shallow soil depth on sloping areas, moderate to steep slopes with elevated erosion risk, and recurrent seasonal inundation in low- lying zones. Land suitability assessment classifies most areas as moderately suitable to marginally suitable for agricultural use, with several units physically unsuitable without engineering measures. These conditions necessitate integrated management approaches combining soil organic matter enhancement, soil and water conservation, land capability-based cropping systems, and spatially informed planning. This study provides a robust biophysical baseline to inform sustainable land management and policy development at the local scale.